Gender Differences in Autism Spectrum Disorder: Exploring the Underdiagnosis and Late Diagnosis of Females - Komilovna , Tuychiyeva Mokhinur; Hazim , Wasim (American Journal of Bioscience and Clinical Integrity, 2025)
Autism Spectrum Disorder (ASD) has historically been diagnosed more frequently in males than females, with a widely cited male-to-female ratio of approximately 4:1. However, emerging research reveals that this disparity may be due, in part, to systemic biases in diagnostic criteria, gendered differences in symptom presentation, and social camouflaging strategies more commonly used by females. This article provides a comprehensive exploration of the gender-based disparities in ASD diagnosis, emphasizing the factors contributing to underdiagnosis and delayed diagnosis in females. Topics include neurobiological and genetic considerations, the limitations of current diagnostic frameworks, cultural and societal influences, and clinical manifestations unique to females. The article also highlights recent advancements in diagnostic tools and proposes future research directions aimed at closing the diagnostic gap and improving outcomes for females on the autism spectrum.